2017
DOI: 10.1177/1073191117715732
|View full text |Cite
|
Sign up to set email alerts
|

Toward Establishing a Standard Symptom Set for Assessing Sluggish Cognitive Tempo in Children: Evidence From Teacher Ratings in a Community Sample

Abstract: Despite increasing interest in sluggish cognitive tempo (SCT) in children, the field is stymied by the lack of a standard symptom set that can be used across studies. Without a standard symptom set, it is difficult to determine if differences across studies are due to methodological or sample differences, or simply the way SCT was measured. To move the field toward a standard symptom set, this study evaluates a teacher-report rating scale of SCT revised based on recent meta-analytic findings that identified op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 53 publications
(140 reference statements)
1
29
1
Order By: Relevance
“…Drawing from studies using these and other SCT measures, meta-analytic findings indicated 13 "constructs" to be optimal for defining the SCT construct -at least as separate from ADHD-IN (see Table 1) [5]. Subsequent studies have simultaneously tested these SCT optimal items and it appears that the field is narrowing in on a standard set of SCT symptoms that can be used across studies [11,29,30].…”
Section: Key Considerations For Examining Sct Within the Dsm Frameworkmentioning
confidence: 99%
“…Drawing from studies using these and other SCT measures, meta-analytic findings indicated 13 "constructs" to be optimal for defining the SCT construct -at least as separate from ADHD-IN (see Table 1) [5]. Subsequent studies have simultaneously tested these SCT optimal items and it appears that the field is narrowing in on a standard set of SCT symptoms that can be used across studies [11,29,30].…”
Section: Key Considerations For Examining Sct Within the Dsm Frameworkmentioning
confidence: 99%
“…Our psychometric analyses showed that two distinct factors underlie the 10-item Attention Problems Scale, one tapping into the typical ADHD symptoms of inattention and hyperactivity/impulsivity and the second into behavior that we may qualify as SCT (Hartman et al, 2004;Lee et al, 2016;Becker et al, 2017;Garner et al, 2017). The distinct nature of the SCT factor was further supported by the low correlation with the factor comprising typical ADHD symptoms.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, based on the results of the PCA, the symptoms violated the assumption of unidimensionality/homogeneity, and one symptom (put symptom here) was performing very poorly. The finding of multidimensionality is not surprising, because items CBCL13, CBCL17, and CBCL80 are part of a set of symptoms that is often used to assess SCT (Becker et al, 2017). Figure 2 shows the graphical displays of the three IRT models fitted to the data in the clinical cohort at T1.…”
Section: Irt Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 75% of students with high levels of SCT are perceived by their teachers as impaired in the peer domain (Becker, 2014). There is not yet consensus as to whether SCT is best defined as a unidimensional or multidimensional construct (Becker, Burns, Schmitt, Epstein, & Tamm, 2017; Becker, Luebbe, & Joyce, 2015; Fenollar Cortés, Servera, Becker, & Burns, 2017; Smith & Langberg, 2017). However, studies using either unidimensional or multidimensional measures of SCT have demonstrated relations with social difficulties.…”
Section: Sct and Children’s Social Functioningmentioning
confidence: 99%